Influence Of Leadership Style And Organizational Culture On Employee Performance Through Work Productivity AtThe Education Office Of South Sulawesi Province - Lili Hartono; Matalatta Matalatta; Hasanuddin Hasanuddin (Vifada Management and Digital Business, 2025)
This study aims to analyze the influence of leadership style and organizational culture on employee performance through work productivity at the South Sulawesi Provincial Education Office. This research was conducted at the South Sulawesi Provincial Education Office for approximately two months, from February to April 2026. The approach used in this study was a quantitative approach with scientific methods. The study population was the head of the office, the head of the division, and all employees of the South Sulawesi Provincial Education Office, with a sample of 135 people determined using a saturated sampling technique. Data collection was conducted through a questionnaire containing questions with a Likert scale to represent respondents' opinions. Descriptive analysis was used to provide an overview of the research variables derived from respondents' answers. Validity and reliability were tested. The data were analyzed using path analysis with the help of SPSS Statistics 22 software. The results showed that leadership style had a positive and significant effect on employee work productivity. Organizational culture also had a positive and significant effect on work productivity. Furthermore, leadership style and organizational culture were shown to have a positive and significant effect on employee performance. Work productivity had a positive and significant effect on employee performance. The results of the indirect effect test indicated that work productivity mediated the relationship between leadership style and employee performance, as well as the relationship between organizational culture and employee performance. Therefore, improving the quality of leadership style and strengthening organizational culture can increase work productivity, which ultimately impacts employee performance. This study implies that organizational leaders need to implement an effective leadership style and build a strong organizational culture to encourage optimal employee productivity and performance.